The Strategic Resources-Criminalization Nexus: Ecuador's Intag Zone∗. Issue 1 (March 2018) - Shade, Lindsay; Ramírez, Darwin Javier
This article draws from the experience of co-author Javier Ramírezwho was detained as a political prisoner for opposition to a large-scale mining project that would displace his community in northern Ecuador. Examining the trajectory of the 20-year mining conflict from the neoliberal era to the present, we argue that there has been a marked shift in the Ecuadorian state's approach to facilitating extractive development, which more directly puts the state's resources in the service of extractive capital through policing and securitization of rural zones and the penalization or criminalization of territorial defense. We outline how "criminalization of protest" actually reflects spatial strategies of securitization and policing to enforce mining rights. The incarceration of Ramírez and deployment of police to secure subsurface rights were strategically timed in a manner to facilitate key administrative and technical requirements for mining permits, making possible the apparently banal but crucial work of consultation and environmental impact studies. We consider the uneven unfolding and spatial differentiation of "resource security" by examining how the state structures and deploys the security apparatus for nature-based commodity investments. We also examine the decreasing public value of mining through the progressive reduction and elimination of taxes, despite continued public investment and military and police support to mining companies. Finally, we contrast state and mining company representatives' efforts to responsibilize the public for demand for commodities with territorial defense strategies which aim to revalue land outside of economistic frameworks.